2020
DOI: 10.46754/jbsd.2020.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Difficulties in Learning of Mandarin Among Foreign-Language Learners and Strategies to Mitigate Them

Abstract: This study explored the hardship faced by foreign-language learners of Mandarin and the strategies applied to overcome them. Literature review found that technology created a positive effect that enhanced the learners’ achievement. Nevertheless, it was still doubtful how far the activities advocated by technology or its potential increase in motivation could boost the students’ learning. Most techniques, real expansions in education and competence had yet to be proven. The hardship and coping strategies were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Instructors need to be creative in minimising the constraints they face, one of which is making good use of technology. For example, in order to overcome the problem of time constraint, activities such as educational games (Chua et al, 2021; Ting & Lam, 2021), flashcards and quizes can be conducted online, outside of class time.…”
Section: Discussionmentioning
confidence: 99%
“…Instructors need to be creative in minimising the constraints they face, one of which is making good use of technology. For example, in order to overcome the problem of time constraint, activities such as educational games (Chua et al, 2021; Ting & Lam, 2021), flashcards and quizes can be conducted online, outside of class time.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it is a challenge for students with the English and Malay background to learn Mandarin. Chua et al (2020), conducted a survey to examine students' view on the challenges in learning Mandarin among non-native students in Universiti Malaysia Terengganu, Kuala Terengganu. 80 participants without the target language knowledge were chosen by purposive sampling technique.…”
Section: Problem Statementmentioning
confidence: 99%
“…Memorizing is a crucial strategy to overcome the setback in learning Mandarin (Chua et al, 2020) due to the characteristics of Mandarin language itself. Graphical organisers are tools for facilitating learning and instruction that combine linguistic forms such as word and phrases to non-linguistic form such as images, symbols, lines to describe content, structure and the key conceptual relationships (Darch & Eaves, 1986).…”
Section: Problem Statementmentioning
confidence: 99%
“…Most of the previous studies conducted by many researchers showed that non-native Chinese learners still have a problem with learning Chinese characters. Also, a lot of students think that the Chinese character is the most challenging part of learning the language, followed by the grammar, vocabulary, intonation, and pronunciation, respectively (Nurul Ain Chua et al, 2020).…”
Section: Problem Statementmentioning
confidence: 99%
“…In the Malaysian context, however, there are some studies on teaching Chinese characters to non-native Chinese learners. According to Ain Chua (2020)…”
Section: Research About Chinese Character Learning Strategymentioning
confidence: 99%